2013
DOI: 10.1038/cddis.2013.40
|View full text |Cite
|
Sign up to set email alerts
|

Human VRK2 modulates apoptosis by interaction with Bcl-xL and regulation of BAX gene expression

Abstract: VRK2 is a novel Ser-Thr kinase whose VRK2A isoform is located in the endoplasmic reticulum and mitochondrial membranes. We have studied the potential role that VRK2A has in the regulation of mitochondrial-mediated apoptosis. VRK2A can regulate the intrinsic apoptotic pathway in two different ways. The VRK2A protein directly interacts with Bcl-xL, but not with Bcl-2, Bax, Bad, PUMA or Binp-3L. VRK2A does not compete with Bax for interaction with Bcl-xL, and these proteins can form a complex that reduces apoptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
44
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 50 publications
2
44
0
2
Order By: Relevance
“…For example, VRK2 has been reported to modulate MAP kinase signaling pathways at the ER, in part via an interaction with the KSR scaffolding protein (41,42). Additionally, VRK2 appears to act as an apoptosis regulator in some studies, inhibiting cell death via interaction with Bcl-xL or by altering BAX gene expression (18). An investigation of these pathways in conjunction with structure/function studies of VRK2 are ongoing in our laboratory.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, VRK2 has been reported to modulate MAP kinase signaling pathways at the ER, in part via an interaction with the KSR scaffolding protein (41,42). Additionally, VRK2 appears to act as an apoptosis regulator in some studies, inhibiting cell death via interaction with Bcl-xL or by altering BAX gene expression (18). An investigation of these pathways in conjunction with structure/function studies of VRK2 are ongoing in our laboratory.…”
Section: Discussionmentioning
confidence: 98%
“…For example, VRK1 is located predominantly in the nucleus, while the major isoform of VRK2 is associated with the endoplasmic reticulum (ER) and nuclear envelope (11,14). Interestingly, both VRK1 and VRK2 possess strong catalytic activity found to modulate cellular processes, including mitosis and apoptosis, via multiple substrates (15)(16)(17)(18). It has also been demonstrated that VRK2 limits cell death during Epstein-Barr virus (EBV) infection (19) and delays myxoma virus replication in a breast cancer cell line (20), thus providing other examples that VRKs may regulate pathways important during viral infection.…”
mentioning
confidence: 99%
“…VRK2 also promotes cancer cell invasion by elevating the transcriptional activity of nuclear factor of activated T cells 1 (NFAT1) by VRK2-mediated phosphorylation (17). In addition, VRK2 prevents apoptosis by interacting with Bcl-x L , an antiapoptotic Bcl-2 homology (BH) domain protein, which is involved in BAX gene expression and regulates mitochondrial function (18). Recently, VRK2 function in the brain has been noted in psychiatric disorders, including schizophrenia and epilepsy.…”
mentioning
confidence: 99%
“…It seems that a subpopulation of VRK2 is localized in the outer mitochondrial membrane. VRK2 was reported to regulate apoptosis through interaction with Bcl-xL in the outer mitochondrial membrane (25). Although VRK2 was observed in the nuclear membrane, it did not perfectly overlap the lamin B (an inner nuclear envelope protein marker).…”
Section: Vrk2 and Chaperonin Tric Interactionmentioning
confidence: 98%
“…VRK2 also inhibits MEK/extracellular signal-regulated kinase signal transduction by interacting with the KSR1 scaffold protein in breast cancer cell lines, which leads to a signaling imbalance (23). In addition, VRK2 enhances cell survival through interacting with BHRF1, an antiapoptotic Epstein-Barr virus protein (24), and Bcl-xL, an antiapoptotic BH (Bcl-2 homology) domain protein (25). Because VRK2 has a sequence similar to that of the catalytic domain of vaccinia-related kinase 1 (VRK1), VRK2 also phosphorylates histone H3 (26), p53 (21), and barrier to autointegration factor (BAF) (27), which supposedly compensates for the VRK1 function.…”
mentioning
confidence: 99%